Measuring bearing currents - Marinov, Pavlik; Rahman, Mohammed Masudur (My University, 2005)
This thesis deals with bearing current detection. It focuses on electric motors driven by variable speed converters. Established techniques for bearing current detection were studied and modified to suit the investigated detecting requirement. The resulting equipment consisted of a mobile sensor, which allows remote detection of discharges taking place inside the motor bearings. Sensors with different characteristics were tested. The new approach for discharge detection was validated performing different tests on motors with different power ratings driven by various frequency converters. The obtained results confirm the possibility of using a universal sensor on motors in the power range from 5-130 kW. The sensor output data can be combined with the data obtained using other sensors, in order to improve the reliability of the results. Two different examples of discharge detection and quantifying devices will be presented. Hopefully, software implementation on one of them will be demonstrated. For current detection a Rogowski coil, a coaxial shunt and current probes were used. The main benefit of using a remote diagnostic device is the removing the need of direct contact to the investigated object and the possible production process interruption. The early detection of bearing currents can have a substantial economical effect when used for early diagnostic and problem finding. This means that the potential problem can be detected before any vibration in the bearing housing occurs. Using advanced calculative methods and additional research, it is believed that the new technique will give satisfactory results in bearing currents measurements
Keywords: Elkraftteknik; Electric power engineering